Questioning Autism’s Racializing Assemblages - Kearl, Benjamin (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2021)
This article questions the ways autism knowledge is racially assembled. Of specific interest is how clinical and cultural definitions of autism routinely deny the existence of autistics of colour and regularly instantiate autism as a White condition. Employing a contrapuntal reading of autism knowledge, which foregrounds the life-writings of autistics of colour, this article argues that disproportionality and delayed autism diagnoses for children of colour as well as autistic Whiteness habituates autism’s diagnostic space. Not only does this result in the clinical and cultural exclusion of children of colour from autism knowledge, it also hierarchically orders humanity. While autism has received recent philosophical attention from Ian Hacking, this article suggests that Hacking’s historical ontology does not adequately attend to the racializing effects of autism knowledge. As such, this article concludes by gesturing toward the need to re-assemble autism’s diagnostic shape through the invention of collective sites of expression which make possible #BlackAutisticJoy.